CSF Neurofilament Light Chain Elevation Predicts ALS Severity and Progression - Sun, Qionghua; Zhao, Xue; Li, Siyuan; Yang, Fei; Wang, Hongfen; Cui, Fang; Huang, Xusheng (Frontiers in Neurology, 2020)
Objectives: This study compared neurofilament light chain (NFL) levels in the cerebrospinal fluid (CSF) of patients with sporadic amyotrophic lateral sclerosis (sALS) with levels in patients with other neurological diseases and healthy controls and assessed correlations between NFL levels and clinical indicators of sALS. Methods: We used enzyme-linked immunosorbent assays to determine the NFL levels in the CSF of 45 patients with sALS, 21 patients with other central nervous system diseases (OCNSDs), 18 with immune-mediated peripheral neuropathy (IMPN), 14 with non-immune-mediated peripheral neuropathy (NIMPN), and 19 healthy controls (HCs). Results: The median NFL levels in the CSF of the sALS, OCNSD, IMPN, NIMPN, and HC groups were 6510, 5372, 4320, 1477, and 756 pg/mL, respectively. The CSF NFL levels did not differ significantly among the sALS, IMPN, and OCNSD groups, but were significantly higher than those of the NIMPN and HC groups. The NFL CSF levels were significantly higher in the NIMPN group than the HCs. There was a negative correlation between the NFL level and ALS function score (ALSFRS-R), and a positive correlation with the disease progression rate in patients with sALS. Conclusion: CSF NFL may not be sufficient to distinguish ALS from other central nervous system diseases or peripheral neuropathy, but it predicts ALS severity and progression.